2010
DOI: 10.1097/tp.0b013e3181ff4ff3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Functional Diversity of Cross-Reactive EBV-Specific CD8+ T Cells in a Longitudinal Study Cohort of Lung Transplant Recipients

Abstract: We report, for the first time, the longitudinal measurement of cross-reactive FLR-specific CD8 T cells within a clinical transplantation framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 41 publications
2
48
1
Order By: Relevance
“…Our previous work has shown the ability of cross-reactive EBVspecific T cells to induce immune reactivity toward HLA molecules expressed on both PBMCs and BAL mononuclear cells (20,23,26). Of particular importance, a seminal study confirmed that recognition of allogeneic HLA molecules by virus-specific memory T cells is dependent on self-peptide presentation by the allogeneic target cell (57).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Our previous work has shown the ability of cross-reactive EBVspecific T cells to induce immune reactivity toward HLA molecules expressed on both PBMCs and BAL mononuclear cells (20,23,26). Of particular importance, a seminal study confirmed that recognition of allogeneic HLA molecules by virus-specific memory T cells is dependent on self-peptide presentation by the allogeneic target cell (57).…”
Section: Discussionmentioning
confidence: 89%
“…Three less frequent TCRs with different TRVab and TRJab usage were also observed, one having public a and b motifs ( n TSYDKV and SSAYYGY, respectively; n = variable number of amino acids) and one having a public a motif ( n GNQF; Table II, underlined). However, after stimulation with C1R.B27 allelic target cells, there was a shift in immunodominance toward clonotypes that had (20,7, and 0%, respectively). In these experiments, CD8 + tetramer + cells were sorted on very low to background levels of IFN-g because of poorer functional responses observed with these subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This will be discussed in more detail for EBV (the second most problematic herpes virus for LTR) in relation to post-transplant lymphoproliferative disease (PTLD) [197][198][199][200]. Importantly, sub-clinical EBV reactivation may also specifically influence lung allograft outcomes through non-lytic virus effects [201,202], stimulating an activated immuno-inflammatory phenotype [203] and the potential for generating crossreactive antiviral memory T-cells [204]. Finally, these concepts are perhaps also important for non-herpes viridae DNA viruses such as human papilloma viruses, hepatitis B and C viruses and parvoviruses, all of which may cause significant problems in individual LTR [205,206].…”
Section: Dna Viruses: CMV Versus Othersmentioning
confidence: 99%